A niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material and a preparation method thereof and a lithium-ion battery containing the same

Through the co-doping method of niobium phosphorus, the shortcomings of nickel-cobalt manganese aluminate materials in terms of circulation and thermal stability are solved, and the efficient preparation of the materials and the improvement of electrochemical performance are achieved.

CN116072857BActive Publication Date: 2025-04-01CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111283765.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-01
Publication Date
2025-04-01
Estimated Expiration
2041-11-01

AI Technical Summary

Technical Problem

Nickel-cobalt-manganese-aluminate materials have shortcomings in cyclic stability and thermal stability, and the traditional co-precipitation preparation method has high requirements and is difficult to adapt to industrial production.

Method used

By co-doping niobium phosphorus, a solid phase ball mill was performed by aluminum-based hydrotalcite nanosheets, nickel-cobalt-manganese ternary precursor and niobium-containing compound, and then mixed with a lithium source to calcinate, and phosphorus-doped heat treatment was carried out in an inert atmosphere to prepare a niobium phosphorus co-doped nickel-cobalt-manganese aluminate quaternary material.

Benefits of technology

It improves the cyclic stability and thermal stability of the material, reduces the difficulty of synthesis, achieves uniform doping of niobium and phosphorus elements, and enhances the electrochemical cyclic stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116072857B_ABST
    Figure CN116072857B_ABST
Patent Text Reader

Abstract

The present invention relates to a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material and a preparation method thereof and a lithium ion battery containing the same. The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material comprises a chemical formula of LiNi x Co y Mn z Al w Nb n P m O 2 Particles, x+y+z+w+n+m=1, 0<y≤0.2, 0<z≤0.1, 0<w≤0.05, 0.002<n≤0.02, 0.001<m≤0.02; A Nb With D Nb The ratio is 0.9-1.1, A P With D P The ratio is 5-15. In the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material of the present application, phosphorus is enriched on the surface of the particles, and niobium is evenly distributed in the bulk phase of the particles. The distribution of the above phosphorus and niobium elements can improve the cyclic stability of the material and alleviate the corrosion of the electrolyte to the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of preparation of positive electrode materials for lithium-ion batteries, and in particular, to a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material, a preparation method thereof, and a lithium-ion battery comprising the same. Background Art

[0002] Since its commercialization, lithium-ion batteries have attracted widespread attention from all walks of life and are currently the main energy supplier for new energy vehicles. As the core component of the battery and the bottleneck of energy density, the performance of lithium-ion battery positive electrode materials directly affects the various performance indicators of lithium-ion batteries. Therefore, positive electrode materials with high specific capacity, good safety, and long cycle life have attracted much attention. As a type of layered positive electrode material, nickel cobalt manganese aluminum oxide material NCMA has the advantages of high specific capacity and good safety performance. However, due to the shortcomings of insufficient structural stability and high surface residual alkali of the layered high-nickel material itself, nickel cobalt manganese aluminum oxide materials face the shortcomings of poor cycle stability and insufficient thermal stability. Element doping is one of the effective methods to improve the structural stability and surface stability of layered materials.

[0003] The niobium-phosphorus co-doping method combines the advantages of each doping element to further improve the material's cycle performance. Patent CN110085858A prepares a nickel-cobalt-manganese ternary precursor by conventional co-precipitation, and then prepares a niobium-phosphorus co-doped nickel-cobalt-manganese ternary positive electrode material through two-step plasma calcination, which improves the structural stability of the material and reduces the residual alkali on the surface. However, the co-precipitation synthesis method of the nickel-cobalt-aluminum ternary system has strict requirements on the reaction conditions. In addition, this method uses conventional co-precipitation to prepare ternary precursors, plasma-enhanced rotary furnaces and other professional equipment, which has high equipment requirements and is not conducive to industrial production. Moreover, it is only subjected to simple surface coating and calcination, which is not conducive to the diffusion of doped ions in the ternary material. Summary of the invention

[0004] The purpose of the present disclosure is to provide a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material and a preparation method thereof and a lithium ion battery containing the same. The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material has good cycle stability.

[0005] In order to achieve the above-mentioned object, the present disclosure provides a quaternary material of nickel-cobalt-manganese-aluminum-lithium co-doped with niobium and phosphorus, wherein the quaternary material of nickel-cobalt-manganese-aluminum-lithium co-doped with niobium and phosphorus comprises a chemical formula of LiNi x Co y Mn z Al w Nb n P m O2 particles, x+y+z+w+n+m=1, 0<y≤0.2, 0<z≤0.1, 0<w≤0.05, 0.002<n≤0.02, 0.001<m≤0.02;

[0006] Among them, A Nb With D Nb The ratio is 0.9-1.1, A P With D P The ratio is 5-15;

[0007] Based on the total molar amount of nickel, cobalt, manganese, aluminum, niobium and phosphorus on the surface of the particles, A Nb represents the molar ratio of niobium element on the surface of the particle, A P represents the molar percentage of phosphorus on the surface of the particle;

[0008] Based on the total molar amount of nickel, cobalt, manganese, aluminum, niobium and phosphorus in the particle phase, D Nb represents the molar ratio of niobium element in the bulk phase of the particle, D P It represents the molar percentage of phosphorus element in the bulk phase of the particles.

[0009] Optionally, the median particle size D50 of the particles is 8-12 μm.

[0010] The second aspect of the present disclosure provides a method for preparing the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material of the first aspect of the present disclosure, the method comprising the following steps:

[0011] (1) performing a first ball milling on aluminum-based hydrotalcite nanosheets, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound to obtain a first pre-product;

[0012] (2) subjecting the first pre-product and the lithium-containing compound to a second ball milling, and then subjecting the first pre-product to a first heat treatment in a first oxygen-containing atmosphere to obtain a second pre-product;

[0013] (3) subjecting the second pre-product and the first phosphorus-containing compound to a third ball milling;

[0014] (4) subjecting the third pre-product obtained in step (3) and the second phosphorus-containing compound to a second heat treatment under an inert atmosphere;

[0015] (5) subjecting the fourth pre-product obtained in step (4) to a third heat treatment in a second oxygen-containing atmosphere;

[0016] The aluminum-based hydrotalcite nanosheets contain a transition metal, the transition metal is a cobalt element or a nickel element, and the molar ratio of the transition metal element to the aluminum element is (2-5):1.

[0017] Optionally, in step (1), the molar ratio of the transition element in the aluminum-based hydrotalcite nanosheets to the niobium element in the niobium-containing compound is greater than 2:1.

[0018] Optionally, the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-a-b Co a Mn b (OH)2 or Ni 1-a- b Co a Mn b CO3, where 0<a≤0.1, 0<b≤0.1;

[0019] Optionally, the median particle size D50 of the nickel-cobalt-manganese ternary precursor is 8-12 μm.

[0020] Optionally, the niobium-containing compound includes one or more of niobium pentoxide, niobium oxalate and ammonium niobium oxalate;

[0021] The lithium-containing compound includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate;

[0022] The first phosphorus-containing compound comprises one or more of ammonium phosphate, diammonium hydrogen phosphate and diammonium dihydrogen phosphate;

[0023] The second phosphorus-containing compound comprises phosphite and / or hypophosphite;

[0024] Optionally, the phosphite includes sodium phosphite and / or ammonium phosphite;

[0025] The hypophosphite includes sodium hypophosphite and / or ammonium hypophosphite;

[0026] Optionally, the molar ratio of the first phosphorus-containing compound to the second pre-product is (0.5-4):100;

[0027] The molar ratio of the second phosphorus-containing compound to the third pre-product is 1:(2-50).

[0028] Optionally, the average particle size of the niobium-containing compound is 50-80 nm; the average particle size of the lithium-containing compound is 6-8 μm; and the average particle size of the first phosphorus-containing compound is 5-10 μm.

[0029] Optionally, in step (2), the molar ratio of the total molar sum of nickel, cobalt, manganese, aluminum and niobium in the first pre-product to the lithium in the lithium-containing compound is 1:(1.0-1.1).

[0030] Optionally, in step (2), the first heat treatment comprises the following steps:

[0031] a. Heating to 500-600°C at a first heating rate of 1-8°C / min for a first calcination for 1-3h;

[0032] b. Continue heating to 700-800°C at a second heating rate of 2-6°C / min and perform a second calcination for 10-15h.

[0033] Optionally, the first ball milling time is 1-4 h; the second ball milling time is 1-4 h; and the third ball milling time is 1-4 h.

[0034] Optionally, step (4) is carried out in a tube furnace, the second phosphorus-containing compound is placed upstream of the tube furnace, and the third pre-product is placed downstream of the tube furnace.

[0035] Optionally, in step (4), the second heat treatment method is roasting, and the conditions of the second heat treatment include: temperature of 200-400° C., time of 3-8 h;

[0036] In step (5), the third heat treatment method is roasting, and the conditions of the third heat treatment include: temperature of 600-850°C and time of 3-8h.

[0037] Optionally, the inert atmosphere comprises nitrogen and / or argon;

[0038] The first oxygen-containing atmosphere and the second oxygen-containing atmosphere are the same or different, and are independently an oxygen atmosphere and / or an air atmosphere.

[0039] A third aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material as described in the first aspect of the present disclosure.

[0040] Through the above technical scheme, the present invention allows aluminum-based hydrotalcite nanosheets containing transition metal elements to react with niobium compounds and nickel-cobalt-manganese ternary precursors under solid phase ball milling conditions, then mix with a lithium source and roast, and finally obtain niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material through phosphorus doping. The above method can reduce the difficulty of material synthesis, improve the doping effect of niobium and phosphorus elements, and further improve the cycle performance of the material. The niobium element in the prepared quaternary material is evenly distributed in the bulk phase, which can inhibit the structural distortion and structural collapse of the material during the charge and discharge process, and improve the cycle stability; the phosphorus element is enriched on the surface of the material, which alleviates the corrosion of the electrolyte to the material, and finally achieves an effective improvement in the electrochemical cycle stability.

[0041] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0043] Figure 1 This is a scanning electron microscope image of the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A1 prepared in Example 1 of the present application.

[0044] Figure 2 This is a scanning electron microscope image of the niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material D1 prepared in Comparative Example 1 of the present application.

[0045] Figure 3 This is a scanning electron microscope image of the phosphorus-doped nickel-cobalt-manganese-aluminum lithium quaternary material D2 prepared in Comparative Example 2 of the present application.

[0046] Figure 4 This is a scanning electron microscope image of the undoped nickel-cobalt-manganese-aluminum-lithium quaternary material D3 prepared in comparative example 3 of the present application. DETAILED DESCRIPTION

[0047] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0048] The present disclosure provides a quaternary material of nickel-cobalt-manganese-aluminum-lithium cobalt-niobium-phosphorus co-doped, wherein the quaternary material comprises a chemical formula of LiNi x Co y Mn z Al w Nb n P m O2 particles, x+y+z+w+n+m=1, 0<y≤0.2, 0<z≤0.1, 0<w≤0.05, 0.002<n≤0.02, 0.001<m≤0.02;

[0049] Among them, A Nb With D Nb The ratio is 0.9-1.1, A P With D P The ratio is 5-15;

[0050] Based on the total molar amount of nickel, cobalt, manganese, aluminum, niobium and phosphorus on the surface of the particles, A Nb represents the molar ratio of niobium element on the surface of the particle, A P represents the molar percentage of phosphorus on the surface of the particle;

[0051] Based on the total molar amount of nickel, cobalt, manganese, aluminum, niobium and phosphorus in the particle phase, D Nb represents the molar ratio of niobium element in the bulk phase of the particle, D P It represents the molar percentage of phosphorus element in the bulk phase of the particles.

[0052] In a preferred embodiment, A Nb With D Nb The ratio is 0.95-1.05, A P With D P The ratio is 6-10. The niobium element of the material within the above range is evenly distributed in the bulk phase, further optimizing the crystal structure of the material, which can inhibit the structural distortion and structural collapse of the material during the charge and discharge process and improve the cycle stability; the phosphorus element is enriched on the surface of the material, alleviating the corrosion of the electrolyte on the material, and ultimately achieving an effective improvement in the electrochemical cycle stability.

[0053] In the present disclosure, “the molar proportion of niobium on the surface of the particle” refers to the ratio of the molar number of niobium on the surface of the particle to the total molar number of nickel, cobalt, manganese, aluminum, phosphorus and niobium on the surface; “the molar proportion of niobium in the bulk phase of the particle” refers to the ratio of the molar number of niobium in the bulk phase of the particle to the total molar number of nickel, cobalt, manganese, aluminum, phosphorus and niobium in the bulk phase; “the molar proportion of phosphorus on the surface of the particle” refers to the ratio of the molar number of phosphorus on the surface of the particle to the total molar number of nickel, cobalt, manganese, aluminum, phosphorus and niobium on the surface; “the molar proportion of phosphorus in the bulk phase of the particle” refers to the ratio of the molar number of phosphorus in the bulk phase of the particle to the total molar number of nickel, cobalt, manganese, aluminum, phosphorus and niobium in the bulk phase

[0054] In one embodiment of the present disclosure, the median particle size D50 of the particles is 8-12 μm, preferably 9-11 μm.

[0055] The second aspect of the present disclosure provides a method for preparing the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material of the first aspect of the present disclosure, the method comprising the following steps:

[0056] (1) performing a first ball milling on aluminum-based hydrotalcite nanosheets, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound to obtain a first pre-product;

[0057] (2) subjecting the first pre-product and the lithium-containing compound to a second ball milling, and then subjecting the first pre-product to a first heat treatment in a first oxygen-containing atmosphere to obtain a second pre-product;

[0058] (3) subjecting the second pre-product and the first phosphorus-containing compound to a third ball milling;

[0059] (4) subjecting the third pre-product obtained in step (3) and the second phosphorus-containing compound to a second heat treatment under an inert atmosphere;

[0060] (5) subjecting the fourth pre-product obtained in step (4) to a third heat treatment in a second oxygen-containing atmosphere;

[0061] The aluminum-based hydrotalcite nanosheets contain a transition metal, the transition metal is a cobalt element or a nickel element, and the molar ratio of the transition metal element to the aluminum element is (2-5):1, preferably (2-3):1.

[0062] During the heat treatment process, the cobalt element or nickel element in the aluminum-based hydrotalcite nanosheets can drive the niobium element into the interior of the material through the "synergistic diffusion effect", reducing the difficulty of synthesizing aluminum-based layered positive electrode materials. And the strong chemical bond of Nb-O can be used to inhibit the structural distortion and structural collapse of the material during the charging and discharging process, thereby improving the cyclic stability of the material. The phosphorus element is mainly enriched on the surface of the particles, which can not only reduce the surface structural damage caused by the water washing and alkali reduction process, but also play a coating effect to alleviate the corrosion of the electrolyte to the material. In the method disclosed in the present invention, phosphorus doping is carried out by solid phase diffusion and vapor phase deposition, which is effective for improving the phosphorus doping effect in the bulk phase of the material and the surface phosphorus enrichment effect. The synergistic effect of multiple phosphorus doping methods can further improve the cyclic performance of the material.

[0063] In the present disclosure, in order to remove surface impurities, step (4) further comprises: cooling the solid material obtained by the second heat treatment to room temperature, adding it to water, stirring and washing for 10 minutes, filtering and drying to obtain a fourth pre-product. The drying method is conventional in the art and is not specifically required here.

[0064] In one embodiment of the present disclosure, in step (1), the molar ratio of the transition metal element in the aluminum-based hydrotalcite nanosheets to the niobium element in the niobium-containing compound is greater than 2:1, preferably greater than 4:1. Meeting the above ratio can reduce the content of niobium element on the surface, so that the prepared material has better electrochemical properties.

[0065] In one embodiment of the present disclosure, the nickel-cobalt-manganese ternary precursor is a high-nickel hydroxide precursor with a chemical formula of Ni 1-a-b Co a Mn b (OH)2, or the nickel-cobalt-manganese ternary precursor is a carbonate precursor with the chemical formula Ni 1-a- b Co a Mn bCO3; wherein, 0<a≤0.1, 0<b≤0.1; further, the nickel-cobalt-manganese ternary precursor is spherical, and its median particle size D50 is 8-12μm, preferably 9-11μm.

[0066] In one embodiment of the present disclosure, the niobium-containing compound includes one or more of niobium pentoxide, niobium oxalate and ammonium niobium oxalate; the lithium-containing compound includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate; the first phosphorus-containing compound includes one or more of ammonium phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate; the second phosphorus-containing compound includes phosphite and / or hypophosphite; further, the phosphite includes sodium phosphite and / or ammonium phosphite; the hypophosphite includes sodium hypophosphite and / or ammonium hypophosphite.

[0067] In one embodiment of the present disclosure, the molar ratio of the first phosphorus-containing compound to the second pre-product is (0.5-4):100; preferably (1-2):100.

[0068] In one embodiment of the present disclosure, the molar ratio of the second phosphorus-containing compound to the third pre-product is 1:(2-50); preferably 1:(5-20).

[0069] In one embodiment of the present disclosure, the average particle size of the niobium-containing compound is 50-80 nm, preferably 50-60 nm; the average particle size of the lithium-containing compound is 6-8 μm, preferably 6-7 μm; and the average particle size of the first phosphorus-containing compound is 5-10 μm, preferably 5-8 μm.

[0070] In one embodiment of the present disclosure, in step (2), the molar ratio of the total molar sum of nickel, cobalt, manganese, aluminum and niobium in the first pre-product to the lithium in the lithium-containing compound is 1:(1.0-1.1), preferably 1:(1.02-1.08), and further preferably 1:(1.04-1.06).

[0071] In the present disclosure, in step (1), the feed amounts of aluminum-based hydrotalcite nanosheets, nickel-cobalt-manganese ternary precursor and niobium-containing compound are LiNi x Co y Mn z Al w Nb n P m The molar ratio of Ni, Co, Mn, Al and Nb in the O2 material can be weighed to meet the molar content of Ni, Co, Mn, Al and Nb in the final product.

[0072] In one embodiment of the present disclosure, in step (2), the first heat treatment comprises the following steps:

[0073] a. Heating to 500-600°C at a first heating rate of 1-8°C / min for a first calcination for 1-3h;

[0074] b. Continue heating to 700-800°C at a second heating rate of 2-6°C / min, and perform a second calcination for 10-15 hours. The above heat treatment method allows the nickel-cobalt-manganese ternary precursor, aluminum-based hydrotalcite nanosheets and lithium-containing compounds to be fully decomposed into oxides in the first calcination stage, improves the solid phase reaction efficiency in the second calcination stage, and generates a layered material with a more complete crystal form.

[0075] In one embodiment of the present disclosure, the first ball milling, the second ball milling and the third ball milling are all solid phase ball milling. Furthermore, the first ball milling time is 1-4h, preferably 2-3h; the second ball milling time is 1-4h, preferably 2-3h; the third ball milling time is 1-4h, preferably 2-3h. Meeting the above ball milling time can ensure sufficient coating and avoid the precursor particles from being broken due to too long ball milling time.

[0076] In one embodiment of the present disclosure, step (4) is performed in a tubular furnace, the second phosphorus-containing compound is placed upstream of the tubular furnace, and the third pre-product is placed downstream of the tubular furnace. The upstream and downstream are arranged relative to the second phosphorus-containing compound, the second phosphorus-containing compound located upstream decomposes under high temperature, and the gaseous phosphide flows to the downstream to react with the third pre-product. By using the above method, phosphorus element is doped into the quaternary material lattice by solid phase diffusion and enriched on the surface of the quaternary material particles by vapor deposition, thereby improving the structure and surface stability of the material.

[0077] In one embodiment of the present disclosure, in step (4), the second heat treatment method is roasting, and the conditions of the second heat treatment include: temperature of 200-400°C, time of 1-5h; preferably, temperature of 300-400°C, time of 2-4h; in step (5), the third heat treatment method is roasting, and the conditions of the third heat treatment include: time of 600-850°C, time of 3-8h; preferably, temperature of 700-800°C, time of 3-5h.

[0078] In one embodiment of the present disclosure, the inert atmosphere includes nitrogen and / or oxygen.

[0079] In one embodiment of the present disclosure, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are the same or different, and are independently oxygen atmosphere and / or air atmosphere. Specifically, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are both oxygen atmospheres.

[0080] In one embodiment of the present disclosure, the following steps are used to prepare aluminum-based hydrotalcite nanosheets containing transition metal elements:

[0081] S1 preparing a first solution comprising a transition metal source and an aluminum source;

[0082] S2: adding the first solution and the alkaline solution into a colloid mill at a speed of 1000-3000 r / min for 2-5 min to obtain a suspension;

[0083] S3 uses the suspension to prepare aluminum-based hydrotalcite nanosheets;

[0084] Further, the use of the suspension to prepare aluminum-based hydrotalcite nanosheets includes: aging the suspension in a water bath at 95-98° C. for 2-4 hours, washing and filtering until the pH is less than 7.5, and drying the filtered solid at 80-120° C. for 8-12 hours to obtain aluminum-based hydrotalcite nanosheets containing transition metal elements. The drying method is conventional in the art and is not specifically required here.

[0085] In the present disclosure, the transition metal source is a soluble transition metal salt, which includes one or more of nickel sulfate, nickel chloride, nickel nitrate and nickel acetate; or, the soluble transition metal salt includes one or more of cobalt sulfate, cobalt chloride, cobalt nitrate and cobalt acetate.

[0086] In the present disclosure, the aluminum source includes one or more of aluminum sulfate, aluminum chloride, aluminum nitrate and aluminum acetate, for example, aluminum sulfate.

[0087] In the present disclosure, the alkaline solution comprises a soluble alkali and a soluble alkaline salt, wherein the soluble alkali comprises sodium hydroxide and / or potassium hydroxide; the soluble alkaline salt comprises sodium carbonate and / or potassium carbonate; specifically, the soluble alkali is sodium hydroxide, and the soluble alkaline salt comprises sodium carbonate. Further, the concentration of the soluble alkali is 1-2 mol / L, and the concentration of the soluble alkaline salt is 0.25-0.75 mol / L.

[0088] In the present disclosure, the volume ratio of the first solution to the alkaline solution is (0.8-1.5):1; for example, they can be mixed in equal volumes.

[0089] In the present disclosure, the molar ratio of the transition metal source calculated as transition metal element to the aluminum source calculated as aluminum element is (2-5):1; the total molar concentration of the transition metal source calculated as transition metal element and the aluminum source calculated as aluminum element is 0.5-1.25 mol / L.

[0090] A third aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material as described in the first aspect of the present disclosure.

[0091] Furthermore, the negative electrode material of the lithium ion battery may be, for example, a lithium sheet, and the electrolyte may be, for example, an alkyl carbonate solution of LiPF6. This is conventional in the art and no specific requirements are made here.

[0092] The reagents used in the examples and comparative examples of the present application are all commercially available.

[0093] The test instrument model of the scanning electron microscope is FEI Quanta 200FEG, the rated voltage of the equipment is 10kV, and the observation is performed at different magnifications;

[0094] The median particle size D50 was measured using a Mastersizer 2000 laser particle size analyzer from Malvern, UK, and the particle size of the nanomaterial was measured using SEM annotation.

[0095] Material metal element analysis: The particle surface element analysis was tested using VG Scientifc's ESCALab220i-XL X-ray photoelectron spectroscopy, and the particle bulk element analysis was tested using a Perkin-Elmer Optima 3300DV inductively coupled plasma (ICP) element analyzer.

[0096] The first discharge capacity and capacity retention rate were tested using Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 2.7-4.3V (vs.Li + / Li). After 5 cycles of charge and discharge at 0.1C, 3 cycles of charge and discharge at 0.2C were performed, and finally a long-term cycle was performed at 0.5C.

[0097] In the following examples and comparative examples, the first ball milling, the second ball milling and the third ball milling are all solid phase ball milling.

[0098] Examples 1-6 are used to illustrate the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material and its preparation method of the present application.

[0099] Example 1

[0100] The following steps are used to prepare niobium and phosphorus co-doped nickel cobalt manganese aluminum lithium quaternary material A1.

[0101] (1) Preparation of Cobalt-Aluminum Hydrotalcite Nanosheets

[0102] Dissolve cobalt sulfate calculated as Co element and aluminum sulfate calculated as Al element in a molar ratio of 3:1 in deionized water to prepare a first solution with a total metal ion concentration of 1.0 mol / L; prepare an alkaline solution with a sodium hydroxide concentration of 1.6 mol / L and a sodium carbonate concentration of 0.25 mol / L. Add the first solution and the alkaline solution at a volume ratio of 1:1 to a colloid mill with a rotation speed of 3000 r / min for a mixed reaction for 3 minutes, stir and age the suspension after the mixed reaction in a 98°C water bath for 3 hours, then wash and filter repeatedly until the pH of the filtrate is less than 7.5, and dry the washed filter cake at 120°C for 10 hours to obtain a cobalt aluminum hydrotalcite nanosheet with a molar ratio of cobalt to aluminum elements of 3:1, with a chemical formula of Co6Al2(OH) 16 CO3·6H2O.

[0103] (2) Niobium doping

[0104] According to Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor (median particle size D50 is 9.5 μm), the cobalt aluminum hydrotalcite nanosheets prepared in step (1), and nano niobium pentoxide (average particle size is 50 nm) are weighed in a molar ratio of 100:1:0.5, and the first ball milling is performed for 2.5 hours to obtain the first pre-product.

[0105] The first pre-product and lithium hydroxide (average particle size is 7 μm) were weighed according to the molar ratio of n(Ni+Co+Mn+Al+Nb):n(Li)=1:1.06, and the second ball milling was carried out for 2.5 hours. Then, the temperature was increased to 500°C in an oxygen atmosphere at a first heating rate of 2°C / min, and the first calcination was carried out for 3 hours. Then, the temperature was continued to be increased to 750°C at a second heating rate of 2°C / min, and the second calcination was carried out for 15 hours. After cooling to room temperature, the second pre-product was obtained.

[0106] (3) Phosphorus doping

[0107] The second pre-product and diammonium hydrogen phosphate (with an average particle size of 5 μm) were weighed at a molar ratio of 100:1, and the mixture was subjected to a third ball milling for 1.5 h to obtain a third pre-product;

[0108] The third pre-product and sodium hypophosphite are weighed in a molar ratio of 20:1, the sodium hypophosphite is placed upstream of the tube furnace, and the third pre-product is placed downstream of the tube furnace, and a second heat treatment is performed under a nitrogen atmosphere by roasting for 2 hours at a temperature of 300° C. After cooling to room temperature, the pre-product is added into water and stirred for washing for 10 minutes, and then filtered and dried to obtain a fourth pre-product;

[0109] The fourth pre-product was subjected to a third heat treatment in an oxygen atmosphere at 750° C. by calcination for 5 hours to obtain niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A1, whose chemical formula, median particle size D50 and element distribution are listed in Table 1.

[0110] The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A1 was tested by scanning electron microscopy. The results are as follows: Figure 1 .

[0111] Example 2

[0112] The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A2 was prepared by the method of Example 1, with the following differences:

[0113] (2) Niobium doping

[0114] According to Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor (median particle size D50 is 9.5 μm), the cobalt aluminum hydrotalcite nanosheets prepared in step (1), and niobium oxalate (average particle size is 50 nm) are weighed in a molar ratio of 100:2:1, and the first ball milling is performed for 2.5 hours to obtain the first pre-product.

[0115] The first pre-product and lithium carbonate (average particle size is 6 μm) were weighed according to the molar ratio of n(Ni+Co+Mn+Al+Nb):n(Li)=1:1.05, and the second ball milling was carried out for 2.5 hours. Then, the temperature was increased to 500°C in an oxygen atmosphere at a first heating rate of 4°C / min, and the first calcination was carried out for 3 hours. Then, the temperature was continued to be increased to 750°C at a second heating rate of 4°C / min, and the second calcination was carried out for 15 hours. After cooling to room temperature, the second pre-product was obtained.

[0116] (3) Phosphorus doping

[0117] The second pre-product and diammonium hydrogen phosphate (with an average particle size of 5 μm) were weighed at a molar ratio of 100:1, and the mixture was subjected to a third ball milling for 1.5 h to obtain a third pre-product;

[0118] The third pre-product and sodium phosphite are weighed in a molar ratio of 10:1, the sodium phosphite is placed upstream of the tube furnace, and the third pre-product is placed downstream of the tube furnace, and a second heat treatment is performed under a nitrogen atmosphere by roasting for 2 hours at a temperature of 400° C. After cooling to room temperature, the pre-product is added into water and stirred for washing for 10 minutes, and then filtered and dried to obtain a fourth pre-product;

[0119] The fourth pre-product was subjected to a third heat treatment in an oxygen atmosphere at 800°C by calcination for 3 hours to obtain niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A2, whose chemical formula, median particle size D50 and element distribution are listed in Table 1.

[0120] Example 3

[0121] The niobium and phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A3 was prepared by the following method.

[0122] (1) Preparation of Cobalt-Aluminum Hydrotalcite Nanosheets

[0123] Dissolve cobalt chloride calculated as Co element and aluminum chloride calculated as Al element in a molar ratio of 2:1 in deionized water to prepare a first solution with a total metal ion concentration of 0.5 mol / L; prepare an alkaline solution with a sodium hydroxide concentration of 1.0 mol / L and a sodium carbonate concentration of 0.5 mol / L. Add the first solution and the alkaline solution at a volume ratio of 1:1 to a colloid mill with a rotation speed of 3000 r / min for a mixed reaction for 3 minutes, stir and age the suspension after the mixed reaction in a 98°C water bath for 3 hours, then wash and filter repeatedly until the pH of the filtrate is less than 7.5, and dry the washed filter cake at 120°C for 10 hours to obtain a cobalt aluminum hydrotalcite nanosheet with a molar ratio of cobalt to aluminum elements of 2:1, with a chemical formula of Co4Al2(OH) 12 CO3·6H2O.

[0124] (2) Niobium doping

[0125] According to Ni 0.8 Co 0.1 Mn 0.1 The CO3 precursor (median particle size D50 is 10 μm), the cobalt aluminum hydrotalcite nanosheets prepared in step (1), and nano niobium pentoxide (average particle size is 50 nm) are weighed in a molar ratio of 100:3:1, and the first ball milling is performed for 2.5 hours to obtain a first pre-product.

[0126] The first pre-product and lithium nitrate (average particle size of 6 μm) were weighed according to the molar ratio of n(Ni+Co+Mn+Al+Nb):n(Li)=1:1.04, and the second ball milling was carried out for 2.5 hours. Then, the temperature was increased to 500°C in an oxygen atmosphere at a first heating rate of 8°C / min, and the first calcination was carried out for 3 hours. Then, the temperature was continued to be increased to 750°C at a second heating rate of 5°C / min, and the second calcination was carried out for 15 hours. After cooling to room temperature, the second pre-product was obtained.

[0127] (3) Phosphorus doping

[0128] The second pre-product and diammonium hydrogen phosphate (with an average particle size of 5 μm) were weighed at a molar ratio of 100:1, and the mixture was subjected to a third ball milling for 1.5 h to obtain a third pre-product;

[0129] The third pre-product and sodium hypophosphite are weighed in a molar ratio of 5:1, the sodium hypophosphite is placed upstream of the tube furnace, and the third pre-product is placed downstream of the tube furnace, and a second heat treatment is performed under a nitrogen atmosphere by roasting for 3 hours at a temperature of 300° C. After cooling to room temperature, the mixture is added into water and stirred for washing for 10 minutes, and then filtered and dried to obtain a fourth pre-product;

[0130] The fourth pre-product was subjected to a third heat treatment in an oxygen atmosphere at 700°C by calcination for 4 hours to obtain niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A3, whose chemical formula, median particle size D50 and element distribution are listed in Table 1.

[0131] Example 4

[0132] The differences of preparing niobium and phosphorus co-doped nickel, cobalt, manganese and aluminum lithium quaternary material A4 by the method of Example 1 are as follows:

[0133] In step (1), cobalt sulfate is replaced with nickel sulfate to prepare nickel-aluminum hydrotalcite Ni6Al2(OH) 16 CO3·6H2O; Ni in step (2) 0.8 Co 0.1 Mn 0.1 The molar ratio of (OH)2 precursor, nickel aluminum hydrotalcite nanosheets, and nano niobium pentoxide is 100:1:0.5. Step (3) is the same as in Example 1. The chemical formula and average particle size of quaternary material A4 are listed in Table 1.

[0134] Example 5

[0135] The niobium-doped nickel-cobalt-manganese-aluminum lithium quaternary material A5 was prepared by the method of Example 3, except that Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of the CO3 precursor, the cobalt aluminum hydrotalcite nanosheets prepared in step (1), and the nano niobium pentoxide is 100:0.5:1. The chemical formula, median particle size D50, and element distribution of the quaternary material A5 are listed in Table 1.

[0136] Comparative Example 1

[0137] In this comparative example, a nickel-cobalt-aluminum-lithium quaternary material D1 is prepared which is not doped with phosphorus but only doped with niobium.

[0138] The quaternary material D1 was prepared by the method of Example 1, except that step (3) was not performed. The chemical formula, median particle size D50 and element distribution of the quaternary material D1 are listed in Table 1.

[0139] The quaternary material D1 was tested by scanning electron microscope, and the results are as follows Figure 2 .

[0140] Comparative Example 2

[0141] In this comparative example, a nickel-cobalt-aluminum-lithium quaternary material D2 is prepared which is doped with only phosphorus element and no niobium element.

[0142] The quaternary material D2 was prepared by the method of Example 1. Steps (1) and (3) were the same as those of Example 1, except that in step (2), Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor (median particle size D50 is 9.5 μm) and the cobalt aluminum hydrotalcite nanosheets prepared in step (1) were weighed in a molar ratio of 100:1 and subjected to the first ball milling for 2.5 h to obtain the first pre-product. The chemical formula, median particle size D50 and element distribution of the quaternary material D2 are listed in Table 1.

[0143] The quaternary material D2 was tested by scanning electron microscope, and the results are as follows Figure 3 .

[0144] Comparative Example 3

[0145] In this comparative example, a nickel-cobalt-aluminum-lithium quaternary material D3 without niobium and phosphorus doping is prepared.

[0146] (1) Preparation of Cobalt-Aluminum Hydrotalcite Nanosheets

[0147] Cobalt sulfate calculated as Co element and aluminum sulfate calculated as Al element were dissolved in deionized water at a molar ratio of 3:1 to prepare a first solution with a total metal ion concentration of 1.0 mol / L; an alkaline solution with a sodium hydroxide concentration of 1.6 mol / L and a sodium carbonate concentration of 0.25 mol / L was prepared. The first solution and the alkaline solution were added to a colloid mill with a rotation speed of 3000 r / min at a volume ratio of 1:1 for a mixed reaction for 3 minutes, and the suspension after the mixed reaction was stirred and aged in a 98°C water bath for 3 hours, and then washed and filtered repeatedly until the pH of the filtrate was less than 7.5, and the washed filter cake was dried at 120°C for 10 hours to obtain cobalt aluminum hydrotalcite nanosheets with a cobalt aluminum molar ratio of 3:1, and the chemical formula was Co6Al2(OH) 16 CO3·6H2O.

[0148] (2) Preparation of nickel-cobalt-manganese-aluminum-lithium quaternary materials

[0149] According to Ni 0.8 Co 0.1 Mn 0.1The (OH)2 precursor (average particle size of 9.5 μm) and the cobalt aluminum hydrotalcite nanosheets prepared in step (1) were weighed in a molar ratio of 100:1, and the two were mixed and solid-phase ball milled for 2.5 hours, and the first ball milling was performed for 2.5 hours to obtain a pre-product.

[0150] The above pre-product and lithium hydroxide (average particle size of 7 μm) were weighed according to the molar ratio of n(Ni+Co+Mn+Al):n(Li)=1:1.06, and the second ball milling was carried out for 2.5 hours, and then the temperature was raised to 500°C at a first heating rate of 2°C / min in an oxygen atmosphere, and the first roasting was carried out for 3 hours, and then the temperature was further raised to 750°C at a second heating rate of 2°C / min, and the second roasting was carried out for 15 hours, and cooled to room temperature to obtain nickel-cobalt-manganese-aluminum-lithium quaternary material D3 without niobium and phosphorus doping. The chemical formula, median particle size D50 and element distribution of the quaternary material D3 are listed in Table 1.

[0151] The quaternary material D3 was tested by scanning electron microscope, and the results are as follows Figure 4 .

[0152] Comparative Example 4

[0153] The method of Example 1 was used to prepare the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D4, with the following differences:

[0154] The sodium hypophosphite in step (3) is replaced with an equimolar amount of diammonium hydrogen phosphate, and the second product and diammonium hydrogen phosphate are subjected to a third ball milling for 1.5 hours to obtain a third pre-product, which is directly heat-treated to obtain niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D4, whose chemical formula, median particle size D50 and element distribution are listed in Table 1.

[0155] Comparative Example 5

[0156] The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D5 was prepared by the method of Example 1, with the following differences:

[0157] The diammonium hydrogen phosphate in step (3) is replaced with an equimolar amount of sodium hypophosphite, the second pre-product is placed downstream of the tubular furnace, the diammonium hydrogen phosphate is placed upstream of the tubular furnace, and a second heat treatment is performed under a nitrogen atmosphere by roasting for 2 hours at a temperature of 300°C. After cooling to room temperature, the mixture is added into water, stirred and washed for 10 minutes, filtered and dried to obtain a fourth pre-product.

[0158] The chemical formula and median particle size D50 of the prepared niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D5 are listed in Table 1.

[0159] Comparative Example 6

[0160] In this comparative example, a conventional solid phase coating method was used to prepare niobium and phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D6.

[0161] (1) Preparation of Cobalt-Aluminum Hydrotalcite Nanosheets

[0162] Cobalt sulfate calculated as Co element and aluminum sulfate calculated as Al element were dissolved in deionized water at a molar ratio of 3:1 to prepare a first solution with a total metal ion concentration of 1.0 mol / L; an alkaline solution with a sodium hydroxide concentration of 1.6 mol / L and a sodium carbonate concentration of 0.25 mol / L was prepared. The first solution and the alkaline solution were added to a colloid mill with a rotation speed of 3000 r / min at a volume ratio of 1:1 for a mixed reaction for 3 minutes, and the suspension after the mixed reaction was stirred and aged in a 98°C water bath for 3 hours, and then washed and filtered repeatedly until the pH of the filtrate was less than 7.5, and the washed filter cake was dried at 120°C for 10 hours to obtain a cobalt aluminum hydrotalcite nanosheet with a molar ratio of cobalt and aluminum elements of 3:1, and the chemical formula was Co6Al2(OH) 16 CO3·6H2O.

[0163] (2) Preparation of nickel-cobalt-manganese-aluminum-lithium quaternary materials

[0164] According to Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor (median particle size D50 is 9.5 μm) and the cobalt aluminum hydrotalcite nanosheets prepared in step (1) are weighed in a molar ratio of 100:1, the two are mixed and solid-phase ball milled for 2.5 hours, and the first ball milling is performed for 2.5 hours to obtain a pre-product.

[0165] The above pre-product and lithium hydroxide (average particle size is 7 μm) are weighed according to the molar ratio of n(Ni+Co+Mn+Al+Nb):n(Li)=1:1.06, and the second ball milling is carried out for 2.5 hours. Then, the temperature is increased to 500°C in an oxygen atmosphere at a first heating rate of 2°C / min, and the first calcination is carried out for 3 hours. Then, the temperature is continued to be increased to 750°C at a second heating rate of 2°C / min, and the second calcination is carried out for 15 hours. After cooling to room temperature, a nickel cobalt manganese aluminum lithium positive electrode material is obtained.

[0166] (3) Doping with niobium

[0167] The nickel cobalt manganese aluminum lithium positive electrode material and nano niobium pentoxide in step (2) were weighed in a molar ratio of 100:0.5, solid phase ball milled for 2.5 hours, and calcined at 750° C. for 5 hours in an oxygen atmosphere to obtain a niobium-doped nickel cobalt manganese aluminum lithium positive electrode material.

[0168] (4) Phosphorus doping

[0169] The doping step of phosphorus element is the same as step (3) of Example 1. The chemical formula, median particle size D50 and element distribution of quaternary material D6 are listed in Table 1.

[0170] Comparative Example 7

[0171] The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D7 was prepared by the method of Example 1, except that the aluminum-based hydrotalcite used was magnesium-aluminum hydrotalcite Mg4Al2(OH) 12 CO3·6H2O, its chemical formula, median particle size D50 and element distribution are listed in Table 1.

[0172] Test Example 1-12

[0173] The quaternary materials of Examples 1-5 and Comparative Examples 1-7 were used as positive electrode materials, mixed with acetylene black conductive agent and polyvinylidene fluoride binder in a mass ratio of 94:3:3, coated on the surface of aluminum foil current collector, dried at 110°C and pressed into sheets, and electrode sheets with a diameter of 1 cm were obtained by a punching machine. The sheets were vacuum dried in a vacuum oven at 120°C for 24 h as positive electrodes, metal lithium sheets were used as negative electrodes, polyethylene films were used as separators, 1 mol / L LiPF6 / (ethylene carbonate + dimethyl carbonate) was used as electrolyte, wherein the volume ratio of ethylene carbonate to dimethyl carbonate was 1:1, and button batteries were assembled in a glove box.

[0174] The Wuhan Blue Electric CT2001A battery tester was used to test the electrochemical performance, and the charge and discharge voltage range was 2.7-4.3V (vs.Li + / Li). After 5 cycles of charge and discharge at 0.1C, 3 cycles of charge and discharge at 0.2C, and finally long-term cycle at 0.5C. The results are listed in Table 1.

[0175] Table 1

[0176]

[0177] According to the data in Table 1, the niobium element in the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary materials A1-A5 prepared by the method disclosed in the present invention is evenly distributed in the bulk phase of the material, and the phosphorus element is mainly concentrated on the surface of the material. Comparing D1 doped with only niobium and D2 doped with only phosphorus, the capacity retention rates of D1 and D2 after 200 cycles are lower than those of A1-A5 co-doped with niobium-phosphorus, but higher than those of D3 without doping, indicating that niobium-phosphorus co-doping can further improve the cycle stability of the quaternary material and has a positive effect on improving the capacity retention rate. In Example A5, the ratio of cobalt element in cobalt-aluminum hydrotalcite to niobium element in niobium pentoxide is 1:1, and the cobalt element is not enough to drive the equimolar number of niobium elements to diffuse synergistically during the solid phase reaction. Therefore, part of niobium in A5 is still enriched on the surface of the material, and effective uniform doping is not achieved. Its capacity retention rate is significantly lower than that of A1-A4. The phosphorus doping method disclosed in the present invention adopts two methods, solid phase diffusion and vapor phase deposition, to carry out phosphorus doping, which is effective in improving the phosphorus doping effect in the bulk phase of the material and the phosphorus enrichment effect on the surface. Compared with the doping method of D4 only solid phase diffusion and D5 only vapor phase deposition, the ratio of phosphorus content on the surface to the bulk phase is A P / D P On the low or high side, it can be seen that its capacity retention rate is significantly lower than A1-A5, indicating that the synergistic effect of multiple phosphorus doping methods can further improve the cycle performance of the material. In D6, the niobium element is enriched on the surface of the material particles, indicating that it is relatively difficult to achieve uniform doping of elements with large ion diameters after the quaternary material structure is formed. Although its first discharge capacity has not changed significantly, its capacity retention rate is significantly lower than that of the uniformly doped embodiment. For the quaternary material D7, magnesium-aluminum hydrotalcite nanosheets that do not contain transition metals are used to prepare the quaternary material, and niobium elements are enriched on the surface of the material particles, which shows that the transition metals in the aluminum-based hydrotalcite nanosheets can drive the niobium element into the interior of the material, so that the niobium element in the prepared material is evenly distributed, thereby obtaining a higher first discharge capacity and good long-term cycle performance. At the same time, the method disclosed in the present invention can flexibly control the ratio of the four elements in the material by changing the type of aluminum-based hydrotalcite nanosheets and the ratio of metal elements to meet the needs of improving the electrical properties of the material.

[0178] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0179] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0180] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum-lithium quaternary material, characterized in that: The method comprises the following steps: (1) performing a first ball milling on aluminum-based hydrotalcite nanosheets, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound to obtain a first pre-product; (2) subjecting the first pre-product and the lithium-containing compound to a second ball milling, and then subjecting the first pre-product to a first heat treatment in a first oxygen-containing atmosphere to obtain a second pre-product; (3) subjecting the second pre-product and the first phosphorus-containing compound to a third ball milling; (4) subjecting the third pre-product obtained in step (3) and the second phosphorus-containing compound to a second heat treatment under an inert atmosphere; (5) subjecting the fourth pre-product obtained in step (4) to a third heat treatment in a second oxygen-containing atmosphere; The aluminum-based hydrotalcite nanosheets contain a transition metal, the transition metal is a cobalt element or a nickel element, and the molar ratio of the transition metal element to the aluminum element is (2-5):1; The molar ratio of the transition element in the aluminum-based hydrotalcite nanosheets to the niobium element in the niobium-containing compound is 2:1 or more; The phosphorus element of the second phosphorus-containing compound is enriched on the particle surface of the quaternary material in a vapor deposition manner; The niobium-containing compound includes one or more of niobium pentoxide, niobium oxalate and ammonium niobium oxalate; The second phosphorus-containing compound comprises phosphite and / or hypophosphite; The phosphite includes sodium phosphite and / or ammonium phosphite; The hypophosphite includes sodium hypophosphite and / or ammonium hypophosphite; The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material comprises a chemical formula of LiNi x Co y Mn z Al w Nb n P m For O2 particles, x+y+z+w+n+m=1, 0<y≤0.2, 0<z≤0.1, 0<w≤0.05, 0.002<n≤0.02, 0.001<m≤0.

02.

2. The method according to claim 1, wherein: The chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-a-b Co a Mn b (OH)2 or Ni 1-a-b Co a Mn b CO3, wherein 0<a≤0.1, 0<b≤0.

1.

3. The method according to claim 2, wherein: The median particle size D50 of the nickel-cobalt-manganese ternary precursor is 8-12 μm.

4. The method according to claim 1, wherein: The lithium-containing compound includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate; The first phosphorus-containing compound comprises one or more of ammonium phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate.

5. The method according to claim 4, wherein: The molar ratio of the first phosphorus-containing compound to the second pre-product is (0.5-4):100; The molar ratio of the second phosphorus-containing compound to the third pre-product is 1:(2-50).

6. The method according to claim 1, wherein: The average particle size of the niobium-containing compound is 50-80 nm; the average particle size of the lithium-containing compound is 6-8 μm; and the average particle size of the first phosphorus-containing compound is 5-10 μm.

7. The method according to claim 1, wherein: The molar ratio of the total molar number of nickel element, cobalt element, manganese element, aluminum element and niobium element in the first pre-product to the molar ratio of the lithium element in the lithium-containing compound is 1:(1.0-1.1).

8. The method according to claim 1, wherein: In step (2), the first heat treatment comprises the following steps: a. Heating to 500-600°C at a first heating rate of 1-8°C / min for a first calcination for 1-3h; b. Continue heating to 700-800°C at a second heating rate of 2-6°C / min and perform a second calcination for 10-15h.

9. The method according to claim 1, wherein: The first ball milling time is 1-4 hours; the second ball milling time is 1-4 hours; and the third ball milling time is 1-4 hours.

10. The method according to claim 1, wherein: Step (4) is carried out in a tube furnace, the second phosphorus-containing compound is placed upstream of the tube furnace, and the third pre-product is placed downstream of the tube furnace.

11. The method according to claim 1, wherein: In step (4), the second heat treatment method is roasting, and the conditions of the second heat treatment include: temperature of 200-400° C. and time of 3-8 h; In step (5), the third heat treatment method is roasting, and the conditions of the third heat treatment include: temperature of 600-850°C and time of 3-8h.

12. The method according to claim 1, wherein: The inert atmosphere includes nitrogen and / or argon; The first oxygen-containing atmosphere and the second oxygen-containing atmosphere are the same or different, and are independently an oxygen atmosphere and / or an air atmosphere.

13. A niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material is prepared by the method according to any one of claims 1 to 12, characterized in that: A Nb With D Nb The ratio is 0.9-1.1, A P With D P The ratio is 5-15; Based on the total molar amount of nickel, cobalt, manganese, aluminum, niobium and phosphorus on the surface of the particles, A Nb represents the molar ratio of niobium element on the surface of the particle, A P represents the molar percentage of phosphorus on the surface of the particle; Based on the total molar amount of nickel, cobalt, manganese, aluminum, niobium and phosphorus in the particle phase, D Nb represents the molar ratio of niobium element in the bulk phase of the particle, D P It represents the molar percentage of phosphorus element in the bulk phase of the particles.

14. The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material according to claim 13, wherein: The median particle size D50 of the particles is 8-12 μm.

15. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material according to claim 13 or 14.

Citation Information

Patent Citations

  • Niobium-phosphorus co-doped high nickel ternary positive electrode material and preparation method and application thereof

    CN110085858A

  • Quaternary positive electrode material for lithium ion battery, preparation method thereof and lithium ion battery

    CN111430700A